(untitled) (LEARNing Landscapes, 2013)
The author, a high school physics teacher, describes the process of teaching with the commercial video game Portal 2. He gives his story from inception, through setbacks, to eventually teaching a semester of laboratories using the Portal 2 Puzzle Maker, a tool which allows for the easy conception and construction of levels. He describes how his students used the Puzzle Maker as a laboratory tool to build and analyze virtual experiments that followed real-world laws of physics. Finally, he concludes with a discussion on the current and future status of video games in education.